Secretin activates brown fat and induces satiation - Laurila Sanna; Sun Lihua; Lahesmaa Minna; Schnabl Katharina; Laitinen Kirsi; Klén Riku; Li Yongguo; Balaz Miroslav; Wolfrum Christian; Steiger Katja; Niemi Tarja; Taittonen Markku; et al. (Springer Nature, 2022)
Brown adipose tissue (BAT) thermogenesis is activated by feeding. Recently, we revealed a secretin-mediated gut–BAT–brain axis, which stimulates satiation in mice, but the purpose of meal-induced BAT activation in humans has been unclear. In this placebo-controlled, randomized crossover study, we investigated the effects of intravenous secretin on BAT metabolism (measured with [18F]FDG and [15O]H2O positron emission tomography) and appetite (measured with functional magnetic resonance imaging) in healthy, normal weight men (GUTBAT trial no. NCT03290846). Participants were blinded to the intervention. Secretin increased BAT glucose uptake (primary endpoint) compared to placebo by 57% (median (interquartile range, IQR), 0.82 (0.77) versus 0.59 (0.53) μmol per 100 g per min, 95% confidence interval (CI) (0.09, 0.89), P = 0.002, effect size r = 0.570), while BAT perfusion remained unchanged (mean (s.d.) 4.73 (1.82) versus 6.14 (3.05) ml per 100 g per min, 95%CI (−2.91, 0.07), P = 0.063, effect size d = −0.549) (n = 15). Whole body energy expenditure increased by 2% (P = 0.011) (n = 15). Secretin attenuated blood-oxygen level-dependent activity (primary endpoint) in brain reward circuits during food cue tasks (significance level false discovery rate corrected at P = 0.05) (n = 14). Caloric intake did not significantly change, but motivation to refeed after a meal was delayed by 39 min (P = 0.039) (n = 14). No adverse effects were detected. Here we show in humans that secretin activates BAT, reduces central responses to appetizing food and delays the motivation to refeed after a meal. This suggests that meal-induced, secretin-mediated BAT activation is relevant in the control of food intake in humans. As obesity is increasing worldwide, this appetite regulating axis offers new possibilities for clinical research in treating obesity.